COGNITIVE ACTIVITY OF STUDENTS UNDER CONDITIONS OF DIGITAL TRANSFORMATION OF LEARNING ENVIRONMENT - Pinchuk O.; Sokolyuk O. (Kherson State University, 2018)
Technological changes in science, economics and society lead to social, political and cultural changes. Changes in education, among other things, cause some contradictions: between the emergence of the latest technology, technology and the new generation of means for training, management and scientific research and late response of education managers to the choice, implementation and spread of innovation; between the need to develop a modern educational environment and the conservatism of leaders and pedagogical staff in the period of innovation transformations. Based on the computer-technology platform of modern education, which acquires characteristics of open, there is a transformation of traditional learning environment into the environment of computer-mediate communication. This environment is characterized by use of distributed educational resources and infrastructures to support educational communities of different types. We consider cognitive activity as an element of the overall learning process, which is a targeted, systematically organized, managed externally or students' individual interaction with the surrounding reality, the result of which is the mastery of scholarly knowledge and work methods at the level of reproduction or creativity. In the process of learning, cognition gets clear form in a special and unique to the person educational and cognitive activity, or learning. The effectiveness of educational and cognitive activity of students in particular is determined by the new paradigm of education of the information society. The entire toolkit is changed, that allow evaluating and controlling educational and cognitive activity. ICT and ICN form new solutions that can influence basic processes in the educational system: formation and development of competencies, recording achievements, learning quality assessment, creating a positive motivation and promoting individual educational and cognitive activities. The article deals with research results of problems of organization of educational and cognitive students' activity and formation of their competencies in the context of transformational changes in the educational process caused by presentation of new technologies.